The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5194/os-10-863-2014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bottom topography on dynamics of river discharges in tidal regions: case study of twin plumes in Taiwan Strait

Abstract: Abstract. The Princeton Ocean Model (POM) is used to investigate the intratidal variability of currents and turbulent mixing and their impact on the characteristics and evolution of the plumes of two neighbouring rivers, the Zhuoshui River and the Wu River, at the central eastern coast of Taiwan Strait. The two estuaries are located close to each other and their conditions are similar in many respects, and yet the two plumes exhibit significantly different behaviour. We explain this through differences of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…Turbid regions associated with river plumes are adjacent to river estuaries and deltas. Spatial and temporal variability of these regions is defined mainly by river discharge rate, turbidity of river water, and local wind forcing [39][40][41][42][43][44][45][46][47]. Coastal erosion in the Laptev and East-Siberian seas is extremely intense due to active thermal abrasion.…”
mentioning
confidence: 99%
“…Turbid regions associated with river plumes are adjacent to river estuaries and deltas. Spatial and temporal variability of these regions is defined mainly by river discharge rate, turbidity of river water, and local wind forcing [39][40][41][42][43][44][45][46][47]. Coastal erosion in the Laptev and East-Siberian seas is extremely intense due to active thermal abrasion.…”
mentioning
confidence: 99%
“…The main advantage of STRiPE lies in its ability to provide realistic results at relatively low computational cost as compared to Eulerian models. The general description of the STRiPE model and some results of its implementation for simulating river plumes in the Black Sea and the South China Sea can be found in Osadchiev and Zavialov (2013) and Korotenko et al (2014).…”
Section: Numerical Simulation Of River Plume Spreadingmentioning
confidence: 99%
“…Therefore, this approach can be used qualitatively on in situ data to investigate the competing processes responsible for changing the stratification. Korotenko (2012) and Korotenko et al (2014) show that vertical mixing due to tide, wind, waves and bottom topography is important for the vertical density structure. They show that bottom topography (a 5 m deep plateau) can play an important role for producing turbulence.…”
Section: Two Parallel Transectsmentioning
confidence: 99%
“…In addition, their studies indicate that a bulk mixing parameterization, such as we applied here, is a rough approximation. However, de Boer et al (2008) used a second-order turbulence model (k-epsilon) in a similar fashion to Korotenko et al (2014) (Mellor-Yamada) to calculate vertical turbulent mixing. In this study, found that the influence of vertical mixing is much smaller than the influence of tidal straining on the evolution of stratification during a tidal cycle.…”
Section: Two Parallel Transectsmentioning
confidence: 99%